Effects of occupational tasks and personal protective equipment on static and functional balance among career firefighters. - Kis, Petra; Abel, Mark; Joyner, Barry; Munkasy, Barry; Melton, Bridget (Ergonomics, 2026)
Musculoskeletal injuries are commonly incurred by firefighters. Most injuries are attributable to overexertion, fall, slip, and trip mechanisms. These injuries may be caused by many factors, including the independent and collective effects of wearing personal protective equipment (PPE) and fatigue induced by performing occupational-tasks. The purpose of this study was to investigate the effect of PPE and fire-suppression tasks on static and functional balance among firefighters. 32 healthy male career structural firefighters (Age: 31.8 ± 9.5 yr) participated in this study. Statistical analyses revealed significant differences in static balance measures pre versus post-work in PPE p ≤ 0.009, and functional balance outcomes pre-work in station uniform versus pre-work in PPE p < 0.001. PPE negatively affected firefighters' functional balance, whereas occupational tasks negatively affected static balance outcomes. These findings highlight the importance of utilising countermeasures to combat occupational fatigue-induced decrements in neuromuscular function to reduce injury risk among structural firefighters. Practitioner Summary: Musculoskeletal injuries are common among structural firefighters and often caused by overexertion, slip, trip, and fall mechanisms; thus, adequate neuromuscular function is crucial to reduce injury risk. There are various factors that affect balance among firefighters while on duty. For example, static balance outcomes are impaired by performing occupational tasks. Although personal protective equipment plays an essential role in safety, it has deleterious effects on firefighters' functional balance.